The design process of a self-propelled floor crane. - Sulaiman, Shamsuddin; Ahmad, Desa; Abdul Aziz, Faieza; Safarzadeh, Daryoush; Majzoobi, Gholam Hossein (2011)
In order to prevent the hazards associated with the crane application in workshops and factories, a self-propelled hydraulic floor crane with wire remote control was designed. The main focus was directed on remote control of the crane operations such as rotation of booms, rear and forward movements, changing travel speed, steering, braking and hook rotation. This configuration prevents the hazards and damages which may be created due to the proximity of operator to crane and provides the feasibility of utilizing the crane in crowded manufacturing areas, fields and hazardous environments. Research into the stability of crane on a slope route was also performed to obtain the equations of stability in static and dynamic conditions and recognition of the ways to enhance the stability. To validate the research work, a scale-model prototype was built to test the manner of controlling the crane operations from afar.